The Individual-Syntactic Relationship in Al-Muqtasid - Mohammed Hamdan Abdullah Abbas, Lect. Dr. (Wasit Journal for Human Sciences, 2025)
This study investigates the lexical-syntactic relationships in Al-Muqtasid fi Sharh al-Idah by Al-Jurjani، aiming to uncover the philosophical dimension in his view of linguistic structures as instruments for constructing meaning. Al-Jurjani adopted an approach founded on the centrality of meaning، which positioned him as a forerunner in employing semantic intuition—an aspect later emphasized by modern linguistics. The research is structured around two main axes: the first examines a set of issues addressed by Al-Jurjani to reveal the lexical-syntactic relationship through syntactic structure، in order to reach a functional interaction based on a balanced system، wherein the structure adapts according to the layering and coherence of linguistic elements، thereby falling within the scope of correctness or otherwise. The second axis addresses other issues to uncover the lexical-syntactic relationship through grammatical inflection (iʿrāb)، demonstrating that it represents semantic relations within the sentence rather than being mere formal markers، and that the grammatical agent (ʿāmil) is subordinate to context and meaning، not an independent governing entity.
Keywords: Al-Jurjani، lexical relationship، syntactic structure، Al-Muqtasid، grammatical inflection